Structural Modeling and Analysis of Flat Wagon Underframe Based on Finite Element Method - Utomo, Ilham Satrio; Marsusiadi, Edi Nyoto; Wibowo, Sulis Tri (Journal of Railway Transportation and Technology, 2025)
This research analyzes the structural strength of the 50-foot Flat Wagon underframe using the finite element method. Modeling was done in Autodesk Inventor and load simulation using ANSYS Workbench with a mesh size of 25 mm. The analysis refers to the UIC 571-4 and EN 12663 standards. The results showed that the maximum stress of 347.56 MPa and maximum deformation of 15.305 mm occurred under combined loading. This value is still below the yield strength of the material (355 MPa), but exceeds 75% of the allowable stress according to KM No. 43 Year 2010 (266.25 MPa). The highest safety factor is 1.82 (compression loading), the lowest is 0.76 (combination loading). This simulation shows the need for design optimization to meet national safety standards..